Strengthening Islamic Values through Islamic Youth Organization Activities - May Maulidia Hana; Ali As’ad (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This research aims to analyze Islamic values within the activities of the Islamic Youth Organization in Banyumanis Village. The focus of Islamic values includes hablumminallah (man's relation with Allah), hablumminannas (interpersonal relations), and hablumminalam (man's relation with the environment). A qualitative method with descriptive approach was employed, gathering data through observations of organizational activities, in-depth interviews with the executives and members, and document analysis. Findings indicate that the organization's activities significantly reflect the practice of Islamic values. Hablumminallah is mirrored in the consistency of worship and religious sessions, hablumminannas is evident from cooperation and social care among members, and hablumminalam is marked by environmental preservation activities. Further discussion delves into the implementation and challenges faced in practicing these values. The conclusion confirms the important role of the Islamic Youth Organization in instilling Islamic values and provides recommendations for the organization's further development to enhance the effectiveness of its activities.